Inhabiting Cyberspace in India
XI, 129 p. 2 illus.
Keywords: This book gathers a selection of essays on the multifaceted aspects of cyber culture in India, both online and offline. It presents an in-depth analysis of cyberspace and its components, while also exploring its lived reality. The respective contributions highlight theoretical perspectives that address questions of relationality regarding all aspects of cyber culture in India, from the physical to the virtual. Bearing in mind India’s vast cultural diversity, which is shaped by different levels of political, social, and economic development, the book offers nuanced studies that analyze the complexities of cyberspace and digital culture in India. The book appeals to all readers interested in technology, cultural studies, online communication networks, feminism, virtual diasporas, and sociology.